ISSUES IN UNDERSTANDING THE COGNITIVE NATURE OF EUPHEMISM IN FOREIGN LANGUAGE TEACHING (Bulletin of Innovative Research, 2026)
this article explores the cognitive nature of euphemism and its role in foreign language teaching. Euphemisms are viewed not merely as lexical substitutions but as cognitively motivated linguistic phenomena shaped by conceptual mechanisms such as metaphor, metonymy, categorization, and cultural models. Understanding euphemism requires awareness of how speakers conceptualize sensitive, taboo, or socially marked topics and encode them in linguistically acceptable forms. In the context of foreign language education, insufficient attention to the cognitive and cultural foundations of euphemism may lead to pragmatic misunderstanding and communicative failure. The study emphasizes the importance of integrating cognitive linguistics and intercultural competence into language teaching practices. By analyzing euphemisms as reflections of speakers’ worldview and conceptual structures, the article highlights their pedagogical value in developing learners’ pragmatic awareness, critical thinking, and communicative appropriateness in a foreign language.